Appreciation of ethrel on ripening dynamic and on the content of ingredients in processing tomato (Lycopersicon lycopersicum (L.) Karsten) varieties - Helyes, L.; Dimény, J.; Lugasi, A.; Schober, Gy.; Pék, Z. (International Journal of Horticultural Science, 2006)
Tomato (Lycopersicon lycopersicum (L) Karsten) is an important crop cultivated in Hungary. Ethrel has been used to advance maturity and promote uniform ripening of processing tomato since 25-30 years in Hungary. The aims of the present study were 1) to evaluate the effects of two different ethrel concentrations on ripening rate, 2) to investigate lycopene content of different maturity stages, 3) to test the effect of ethrel on lycopene content. It is important to note that the experimental year (in July and August) was very rainy and cool. Ethrel was applied at two rates: 1500 and 3000 ppm. The results clearly indicate that Ethrel can be a useful and effective tool of maturity-enhancement, under present circumstances. Ripening concentration increased significantly by Ethrel. In spite of this, Ethrel treatments did not affect lycopene content of examined varieties significantly. The quality of tomato products are characterised by their lycopene content. Colour is highly important quality factor of food products. The range in lycopene contents from all samples evaluated was 48.7 to 113.0 mg kg-1 fresh weight. Also correlations between lycopene content and colour (a*/b*, and chroma) were investigated also.